PENGARUH STRATEGI PEMBELAJARAN DAN KECERDASAN GANDA TERHADAP HASIL BELAJAR IPS SISWA KELAS XI SMK NEGERI 1 MERANTI - Siregar, Maulina (TABULARASA, 2014)
The population of this research is all students in the eleventh grade of SMK Negeri 1 MerantiÂ consist of 5 classes or 170 students. The samples of this research are the students of the eleventh grade consist of 2 classes. The sampling technique used is cluster random sampling. This research method used quasi-experimental design with factors 2 Ã 2. The instruments used are IPS result test for 32 valid questions of multiple choice with four options and Multiples intelligence questionnaires for 35 questions with 2 options (choice a and b). The technique of data analysis used is two ways ANOVA in significance level ofÂ  Î± = 0.05. The research result shows that: 1) the studentsâ achievement of IPS Â taught by using Â NHT learning strategy (average is 81.95) is higher than the students Â who are taught by using STAD Learning Strategy (average isÂ  79.10) ; 2) The students achievement who have interpersonal intelligence (average is 84.06) is higher Â than the students who have intrapersonal intelligence (average is 77.64); and Â 3) there is interaction between NHT learning strategy and STAD learning strategy and multiples intelligence (intrapersonal and interpersonal intelligence) towards studentsâ IPS achievement. Based on the studentsâ average mark it gives indication that students group who has interpersonal intelligence will be better taught by using NHT learning strategy and the students who have intrapersonal intelligence will be better taught by using STAD learning strategy.